Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study. Issue 2 (1st February 2023) - Hu, Jia-Ling; Duan, Yipin; Zhong, Huai-Ning; Lin, Qin-Bao; Zhang, Tianlong; Zhao, Chuang-Chuang; Chen, Sheng; Dong, Ben; Li, Dan; Wang, Jing; Mo, Ming-Zhen; Chen, Jie; et al.
Abstract: Plastic take-out food containers may release microplastics (MPs) into food and pose a potential risk to food safety and human health. Here, after being subjected to hot water treatment, MPs released from three types of plastic food containers (polypropylene, PP; polyethylene, PE; expanded polystyrene, EPS) were identified by micro-Raman spectroscopy. The results showed that the size of released MPs ranged from 0.8–38 μm and over 96% MPs were smaller than 10 μm. Various MPs concentrations were found from the three types of containers, that is, 1.90 × 10 4, 1.01 × 10 5, and 2.82 × 10 6 particles/L on average from PP, PE, and EPS, respectively. Moreover, based on thermal and morphology analysis, we discovered that both relaxations of the polymer chains in the rubbery state and defects caused by processing techniques might contribute to the release of MPs. Thus, such release can be reduced by increasing the thermal stability of the materials and mitigating the defects generated during production.